Analisis Pengaruh Motivasi, Kepemimpinan, Dan Budaya Organisasi Terhadap Kinerja Perawat (Studi Pada RSUD Ambarawa) (Students' Journal of Economic and Management, 2015)
This study analyzed the influence of motivation, leadership, and organizational culture on nurses performance. The object of this research is Ambarawa Hospital. The population in this study was a nurse at the hospital Ambarawa amounted to 208 people. While the sample is determined by using the Solvin formula  by 65 respondents. The purpose of research is used to know the influence of motivation, leadership, and organizational culture to performance of nurses. The data were analyzed using validity testing, reliability testing, and regression to test and prove the research hypothesis.The conclusion of this study are as follows: (1) Motivation positive and significant impact on the performance of nurses (2) Leadership positive and significant impact on the performance of nurses (3) Organizational Behavior positive and significant impact on the performance of nurses.Keywords: Motivation, Leadership, and Organizational Culture